Edukasi Gemini Insan (Gerakan Perempuan Mahir Literasi dan Inklusi Keuangan) Kelompok Ibu-Ibu PKH Kecamatan Singaparna Kabupaten Tasikmalaya - Edi Fitriana Afriza; Redi Hermanto; Oka Agus Kurniawan Shavab; Dede Wahyu Firdaus; Gugum Gumilar; Sri Hardianti Sartika (JURPIKAT (Jurnal Pengabdian Kepada Masyarakat), 2025)
The purpose of the activity is to provide benefits for KPM PKH mothers in increasing knowledge and insight into family financial management, banking and non-bank financial services, financial decision-making and monthly budget making that form a strong foundation for family financial resilience. The Participatory Action Research (PAR) approach is used in PKM activities, through five stages of activities, including 1) Partner cooperation; 2) Pre-abdimas (Determining materials, designing pretests and scheduling activities); 3) Implementation of PKM activities; 4) Evaluating educational activities through Postes and 5) Preparation of reports and publications. The results of the 30 participants were given a pretest, as many as 14 people had low financial literacy and inclusion knowledge, 10 people had moderate financial literacy and inclusion knowledge, the remaining 6 people understood the importance of financial planning and management. The results of the post were obtained by around 24 people who experienced an increase in understanding of financial literacy and inclusion, 3 people still have moderate financial literacy and inclusion and also 3 people are still relatively low